Corrosion in fire protection systems in an offshore unit undergoing decommissioning - Araujo, Leonardo Silva; Mounzer, Elie Chahdan; Wavrik, Jennifer Rosy Avelino (Acta Scientiarum. Technology, 2025)
The present study addresses corrosion in critical safety systems on an offshore oil and gas platform of the Floating Production Storage and Offloading type. The platform is over 25 years old and is currently being decommissioned. Corrosion on offshore platforms is of significant concern because of the risks associated with compromised mechanical integrity or functionality of fire protection systems. Such compromises can lead to property damage, environmental damage, worker health risks and escalation of fire-related emergencies. To achieve the aims of this study, a bibliographic search was conducted from 2017 to 2023. In addition, other relevant search sources were considered. These included accident data collected by the Brazilian National Agency for Petroleum, Natural Gas, and Biofuels, which is responsible for regulating, contracting, and supervising economic activities in the petroleum industry. Field research was also conducted to assess the operating conditions and integrity of both fixed and portable firefighting systems, as well as the damage caused by corrosive processes in these systems. Ultimately, the study concludes that operators in exploration and production fields are genuinely concerned about the integrity of their systems during the decommissioning process. This concern is aimed at preventing harm to people, the environment, and the company’s assets. In addition, operators seek to avoid incidents that could negatively impact the company’s reputation with society, investors, and regulators.